Strongly Singular Convolution Operators on Herz-Type Hardy Spaces with Variable Exponent - Hongbin Wang; Dunyan Yan (Journal of Function Spaces)
We investigate the boundedness of the strongly singular convolution operators on Herz-type Hardy spaces with variable exponent.